2009
DOI: 10.21273/hortsci.44.5.1461
|View full text |Cite
|
Sign up to set email alerts
|

‘Harovin Sundown’ Pear

Abstract: Additional index words. Pyrus communis, fire blight, Erwinia amylovora, resistance 'Harovin Sundown' pear (Pyrus communis L.) is an attractive late-season fresh market pear with good storage capability. It is highly productive with no evidence of biennial bearing. The tree has excellent resistance to fire blight [a bacterial disease incited by Erwinia amylovora (Burr.) Winslow et al.]. This new cultivar, developed by Agriculture and Agri-Food Canada (AAFC) at its Research Centers in Harrow and Vineland Station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Our previous research revealed that 1-MCP and storage at 0 °C, 2.5 kPa O 2 and 2 kPa CO 2 effectively controls the development of senescent scald and internal breakdown in 'Swiss Bartlett' and 'Cold Snap' pears (Lum et al 2017). 'Cold Snap' and 'AC Harrow Crisp' are newly developed Ontario pear cultivars that are resistant to fire-blight (Hunter et al 2002(Hunter et al , 2009, which is an orchard-borne disease leading to widespread economic losses in the production of traditional cultivars, such as 'Bartlett'. 'AC Harrow Crisp' is a midseason pear with highly preferred flavour and texture properties (Hunter et al 2002).…”
mentioning
confidence: 99%
“…Our previous research revealed that 1-MCP and storage at 0 °C, 2.5 kPa O 2 and 2 kPa CO 2 effectively controls the development of senescent scald and internal breakdown in 'Swiss Bartlett' and 'Cold Snap' pears (Lum et al 2017). 'Cold Snap' and 'AC Harrow Crisp' are newly developed Ontario pear cultivars that are resistant to fire-blight (Hunter et al 2002(Hunter et al , 2009, which is an orchard-borne disease leading to widespread economic losses in the production of traditional cultivars, such as 'Bartlett'. 'AC Harrow Crisp' is a midseason pear with highly preferred flavour and texture properties (Hunter et al 2002).…”
mentioning
confidence: 99%
“…Senescent scald development was negatively associated with changes in glutathione levels; more moderate relationships were apparent for the other storage-related disorders (Figure ). Similarly, these metabolic phenomena occur in advance of internal breakdown and senescent scald symptoms in ‘Cold Snap’ and ‘Swiss Bartlett’ pear fruit, cultivars that are genetically related to ‘AC Harrow Crisp’. , A moderate association was apparent between glutathione and ascorbate metabolites; however, GSH levels were generally better maintained than those of AsA. It is tempting to speculate that the maintenance of GSH levels in stored ‘AC Harrow Crisp’ fruit is due to a malfunction in the AsA recycling pathway, including DHA reductase, which is involved in the reduced GSH-mediated regeneration of reduced AsA from DHA .…”
Section: Discussionmentioning
confidence: 99%
“…Bartlett and Bosc represent 95% of current pear production by area; however, these cultivars are prone to fire blight [Erwinia amylovora (Burrill) Winslow et al] and as a result, growers are hesitant to plant them. There is interest in the recent introduction of AC Harovin Sundown (Cold Snap™) (Shaw 2017), a cultivar which is both winter hardy and less susceptible to fire blight (Hunter et al 2009).…”
Section: Introductionmentioning
confidence: 99%